(untitled) (Journal of the College of Education for Women, 2021)
The study aims to identify the impact of electronic games on increasing the dropout rate among students in the basic stage in Jordan from their teachers’ point of view. The study adopted a descriptive survey method. Its community consisted of all fe(male) teachers of the basic stage in public and private schools, (First Amman, Irbid, and special education in Zarqa and Amman). The electronic questionnaire was used as a tool for the study. The results have shown that the effect of electronic games on increasing the dropout rate among students in the basic stage in Jordan was high. Besides, there are statistically significant differences due to the gender variable for males. There are statistically significant differences due to the variables of the school sector and private schools. Besides, there are statistically significant differences due to the variable of specialization and in favor of humanities. The study finally recommended to have more stringent controls by the Ministry of Education on dropout students. It has further recommended to activate the role of the educational counselor in educating students about electronic games, and hold workshops for them on how to invest time properly